The Mission : Waging War and Keeping Peace with America's Military - Priest, Dana (New York W.W. Norton & Company, 2003)
An account of America's growing dependence on its military to manage world affairs describes the cultural clashes experienced by the nation's generals, soldiers, and Green Berets in eighteen different countries.
Include Illustration, Note and Index
Keywords: World politics -- United States -- Armed Forces--Foreign service